2014
DOI: 10.1136/bcr-2014-203874
|View full text |Cite
|
Sign up to set email alerts
|

A case of sigmoid colon duplication in an adult woman

Abstract: Colonic duplication is a rare congenital anomaly that is often diagnosed in childhood, but may go unrecognised until adulthood. It often presents with chronic abdominal pain and constipation, and the preoperative diagnosis may be difficult. We present a case of sigmoid duplication in a 33-year-old Indonesian woman who presented with right-sided colicky abdominal pain and vomiting. Clinical examination was unremarkable and radiological investigations raised the possibility of a giant colon diverticulum. The pat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
12
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 26 publications
1
12
0
Order By: Relevance
“…In 2010, Mourra et al 4 reviewed seven cases of colorectal duplication, but only one of them was a case of sigmoid duplication that had a preoperative diagnosis of colonic duplication. In 2014, Al-Jaroof et al 9 reported a case of sigmoid tubular duplication in a 33-year-old woman who underwent an exploratory laparotomy that confirmed the diagnosis 9. In this particular case, the diagnosis of colonic duplication was in the differential diagnosis, along with a giant diverticulum, volvulus and duplication cyst.…”
Section: Discussionmentioning
confidence: 91%
“…In 2010, Mourra et al 4 reviewed seven cases of colorectal duplication, but only one of them was a case of sigmoid duplication that had a preoperative diagnosis of colonic duplication. In 2014, Al-Jaroof et al 9 reported a case of sigmoid tubular duplication in a 33-year-old woman who underwent an exploratory laparotomy that confirmed the diagnosis 9. In this particular case, the diagnosis of colonic duplication was in the differential diagnosis, along with a giant diverticulum, volvulus and duplication cyst.…”
Section: Discussionmentioning
confidence: 91%
“…The real challenge for the surgeon is the clinical and radiological diagnosis before the definite treatment. It's more applicable in the case of Y shape colonic duplication as in this patient [1] The CT or MRI after Barium enema administration demonstrating the additional intestinal loop arising from the native colon or the bifurcation of colonic lumen detected during colonoscopy examination will help to diagnose the colonic duplication before definitive treatment. The radiological diagnosis was made as highly suspicious of chronic intussusception of the small intestine in this patient.…”
Section: Discussionmentioning
confidence: 91%
“…Colorectal duplication is the least common type among gastrointestinal duplication. A wide spectrum of clinical presentation and radiological features of colonic duplication is creating diagnostic difficulties for surgeons and radiologist [1].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Another rare, yet possible malformation during colonic embryonal development is colonic duplication. The extra lumen may be spherical or tubular and it may or may not communicate with the major lumen (180). However, to date, no clear etiology for this condition has been recognized.…”
Section: Molecular Control Of the Radial (Rad) Patternmentioning
confidence: 99%